Sanctions for Zina Perpetrators: A Review of Interfaith Couples from the Perspective of the Criminal Code and Fiqh Jinayah - Istikhomariyah Istikhomariyah; Iwan Iwan (Al-Adalah: Jurnal Hukum dan Politik Islam, 2025)
This study analyzes the sanctions for adultery in interfaith marriages based on the Indonesian Criminal Code (KUHP) and Islamic criminal law (fikih jinayah). Using a normative legal method, this research applies both Islamic law and comparative law approaches to evaluate the differences in the regulation of adultery within the two legal systems. The data sources consist of primary legal materials (KUHP, Compilation of Islamic Law, the Book of Fikih Jinayah, and the Marriage Law) and secondary legal materials (academic literature and court decisions). The analysis is conducted descriptively-analytically using the triangulation of legal sources technique. The findings show that the KUHP only criminalizes adultery as infidelity within a marriage, whereas in fikih jinayah, any sexual relationship outside a lawful marriage is considered adultery. In Islam, interfaith marriage is not recognized. Thus, such a relationship is categorized as adultery. In contrast, under Indonesia's positive law, interfaith marriages can still be recognized through specific legal mechanisms. Additionally, apostasy (murtad) has different legal consequences: In fikih jinayah, the marriage is automatically annulled, while under the KUHP, the marital status remains valid until a court decision is made. This inconsistency presents challenges in harmonizing national criminal law. Legal reform is needed to balance social norms, state law, and the principles of Sharia to create a more inclusive legal system that is adaptive to the needs of Indonesian society.